2024
DOI: 10.62110/sciencein.jist.2024.v12.752
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome (PCOS) and oxidative stress

Pallav Sengupta,
Sulagna Dutta,
Muhjah Fallah Hassan

Abstract: Polycystic Ovary Syndrome (PCOS) affects about 10% of women of reproductive age, characterized by hyperandrogenism, anovulation, and polycystic ovaries. Despite extensive research, its etiology remains uncertain with genetic, metabolic, and environmental factors implicated. This review explores the relationship between PCOS and oxidative stress (OS), focusing on molecular pathways and their effects on reproductive physiology. OS arises from an imbalance between reactive oxygen species (ROS) production and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…In reality, PCOS is linked to reproduction, metabolic, psychological dysfunction, and clinical complications examples include reduced tolerance for glucose and diabetes, hypertension, severe cardiovascular disease, chronic oligo-ovulation, infertility, anovulation, and ovarian cancer. Despite a lengthy history of research on PCOS, the aetiology is yet unclear, but have revealed involvement in an inflammatory state, endothelial injury, oxidative stress [OS], in addition genetic pathways [4,5]. markers are much greater in women with PCOS than in the general population, and they are now recognized as a possible cause of PCOS aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, PCOS is linked to reproduction, metabolic, psychological dysfunction, and clinical complications examples include reduced tolerance for glucose and diabetes, hypertension, severe cardiovascular disease, chronic oligo-ovulation, infertility, anovulation, and ovarian cancer. Despite a lengthy history of research on PCOS, the aetiology is yet unclear, but have revealed involvement in an inflammatory state, endothelial injury, oxidative stress [OS], in addition genetic pathways [4,5]. markers are much greater in women with PCOS than in the general population, and they are now recognized as a possible cause of PCOS aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unstable and highly reactive nature, peroxides and free radicals have the potential to damage various cellular components, with DNA damage having particularly concerning long-term consequences. (Sengupta et al , 2024 ;Darbandi et al , 2018 ;Alahmar and Sengupta , 2021 ) . OS is believed to be a potential triggering factor in the pathophysiology of PCOS.…”
Section: Introductionmentioning
confidence: 99%